Efficacy and safety of antivirals in treating hearing loss: A systematic review and network meta-analysis - Liu, Li-Mei; Xia, Li-Li (Frontiers in Neurology, 2022)
Objectives This study aimed to compare and rank the therapeutic effects of antivirals in treating hearing loss using a network meta-analysis approach. Methods We searched the PubMed, Embase, and Cochrane Library databases to identify eligible randomized controlled trials (RCTs) through April 2022. Placebo-controlled or head-to-head RCTs of three categories of antivirals for hearing loss were included, and pooled relative risks (RRs) with 95% confidence interval (CI) were calculated using pairwise and network meta-analyses. Results Six RCTs with 405 patients were included in the final analysis. The results showed that ganciclovir had relatively better effects on the incidence of hearing recovery (surface under the cumulative ranking: 88.8%) compared with other antivirals. However, pairwise comparison analyses found that the use of antivirals significantly increased the incidence of hearing recovery compared with the use of a placebo (RR: 1.27; 95% CI: 1.04–1.54; P = 0.017), while no significant difference was observed between any two categories of antivirals. Finally, the use of antivirals did not increase the risk of adverse events compared with the use of a placebo (RR: 1.27; 95% CI: 0.82–1.98; P = 0.285). Conclusion Antivirals are more efficacious than placebos for hearing recovery in patients with hearing loss, and ganciclovir is the most likely to increase the incidence of hearing recovery.